Efficacy and Safety of In-Asia-manufactured Interferon alpha-2b in Combination with Ribavirin for Therapy of Naïve Chronic Hepatitis C Patients: A Multicenter, Prospective, Open-Label Trial - Nurul Akbar; Ali Sulaiman; Rino Alvani Gani; Irsan Hasan; Laurentius Lesmana; Andri Sanityoso; Sjaifoellah Noer; FX Pridady; Soemarno Soemarno (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Background: An open-label, multi center and non-comparative study was conducted to evaluate the efficacy and safety of a more affordable in-Asia-manufactured interferon á-2b product in combination with ribavirin to treat naïve chronic hepatitis C patients. Method: Thirty chronic naïve hepatitis C patients were treated with in-Asia-manufactured interferon   a-2b subcutaneously 3 MIU thrice weekly and ribavirin 800-1,200 mg daily for 48 weeks. Follow-up was done until 24 weeks after the end of treatment. Efficacy was assessed by examining serologic and biochemical parameters at pre and post-treatment. Safety was assessed by evaluating clinical symptoms and laboratory parameters. Results: The virological response and sustained virological response rates of all Hepatitis C Virus (HCV) genotypes were 83.3% and 76.7% respectively. Post-treatment, 80% patients had significant alanine transaminase (ALT) decreased into normal level and remained normal in 76.7% patients at 24th week follow up period. At that time, the ALT level and sustained virological response were lower in HCV genotypes 1 and 4 than in non-1 and non-4 genotypes. The most frequent adverse event was flu-like syndrome. Conclusion: The efficacy and safety study on combination therapy of in-Asia-manufactured interferon a-2b and ribavirin has shown a good result based on the current standard of interferon alpha and ribavirin combination therapy. Keywords: interferons, combination drug therapy, chronic hepatitis C, treatment efficacy, safety